Semiconducting polymer nanoparticles as photoacoustic molecular imaging probes. (27th June 2016) - Cui, Liyang; Rao, Jianghong
Abstract : As an emerging class of optical nanomaterials, semiconducting polymer nanoparticles (SPNs) are highly photostable, optically active and versatile in chemistry; these properties make them attractive as molecular imaging agents to enable imaging of biological events and functionalities at multiple scales. More recently, a variety of SPNs have been found to exhibit high photoacoustic properties, and further empowered photoacoustic imaging for contrast enhanced in vivo molecular imaging. Target‐sensitive components can be incorporated in the SPNs to create activatable imaging probes to sense and monitor the target dynamics in living objects. Intrinsically biophotonic and biocompatible, SPNs can be further engineered for multimodal imaging and for real‐time imaging of drug delivery. WIREs Nanomed Nanobiotechnol 2017, 9:e1418. doi: 10.1002/wnan.1418 This article is categorized under: Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Abstract : Semiconducting polymeric nanoplatform for photoacoustic imaging